Trichoteiromania in a 7-year-old girl. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
In this child, we excluded the suspect of ring-worm due to the lack of broken-off hairs and negativity of the direct mycological examination. We excluded the diagnosis of alopecia areata due to the presence of mild scaling inflammation and the absence of exclamation mark, cadaverized hairs and yellow dots. We excluded the diagnosis of trichotillomania because the hairs had all the same length and there were no broken hairs. The dermoscopic findings were very similar to that observed in alopecia due to break dance because of the presence of mild scaling inflammation and thinned hairs, possibly because of the inflammation itself. The presence of a squamous crust led us to consider the role of repeated scratching and our suspicion was confirmed by the observations of the teacher and father. Trichoteiromania has been already described in adults with psychiatric problems (1, 2) but not in the child.